STUDENTS’ PERCEPTION TOWARDS TEACHER’S STRATEGY AT THE COVID-19 PANDEMIC - Latala, Ilham; Tuna, Jim Ronny; Liando, Nihta V. F. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The purpose of this study is to find out the students’ perception toward teachers’ role in motivating students to learn English during the Covid-19 pandemic. In this research, researchers use the qualitative method. To collect the data, the researchers used a questionnaire that consists of 10 questions. The population of this study is the students at SMP Negeri 2 Tondano and the samples are the 8th grade students with a total of 23 students. The samples chosen are the active students who follow the teaching and learning process in their school in online and offline ways. The findings show that students are having great experiences in teaching and learning English. In general, the students respond to the statements very well with positive responses dominated by Agree and Strongly Agree. It showed that the students’ perceptions of the teacher’s role in English learning are various in the Covid-19 pandemic situation. In general, Covid-19 had a significant impact on the world of education, including in the educational system in Indonesia. Traditional and routine learning that emphasizes the interaction of teachers and students in the classroom and outside the classroom shifts to distance learning.